PENGGUNAAN MEDIA POSTER UNTUK MENINGKATKAN MINAT SISWA TERHADAP LITERASI PADA SISWA KELAS IV DI SDN TANJUNG VI: THE USE OF POSTER MEDIA TO INCREASE STUDENTS' INTEREST IN LITERACY IN GRADE IV STUDENTS AT SDN TANJUNG VI - Setiarini, Yayuk; Setyawan, Agung (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
Students' interest in reading and writing was found to be quite low, with the percentage of interest in reading and writing ranging from 60% to 65%, according to observations made in Class IV of SD Negeri Tanjung VI. This is because the School Literacy Movement (GSL) is only implemented in the classroom and is limited to textbooks. Since most of the things that children use are text-based, as a result they become disinterested in reading very quickly. This study aims to find out and describe the effect of using posters as a tool to increase students' enthusiasm for reading at SDN Tanjung VI. All eight Grade IV students at SDN Tanjung VI constituted the study population, and a total sampling technique (also known as saturated sampling) was used. This study falls under the category of classroom action research (CAR) and used data collection methods, including documentation, questionnaires, interviews, and observation. Questionnaires and observation sheets were among the research tools. Quantitative descriptive analysis was used to examine the collected data. The results showed that the use of posters increased literacy interest, both in Cycle I and Cycle II. Students' enthusiasm in reading and writing literacy increased from 72% in Cycle I to 85% in Cycle II. This finding shows that students' enthusiasm in reading and writing literacy was positively influenced by the use of posters.